Hugo Mayo - Fernández, María Del carmen (Revista Universidad de Guayaquil, 1988)
Number 14 of the LA ROSA DE PAPEL Collection includes the latest poetic production by Hugo Mayo. The pamphlet consists of 25 poems, selected and prefaced by Carlos Calderón Chico. In the preliminaries, the aforementioned scholar locates to the poet in his historical-literary context. Mayo, a rebel, denies all the hackneyed formulas of the poetry that is contemporary to him in Ecuador and seeks, beyond the borders, contact with other innovators of artistic creation.